Harnessing the Influence of Social Media Marketing Activities: Enhancing Brand Loyalty Through Brand Awareness and Brand Image Among Le Minerale Consumers in Medan - Vanny Lim; Yolanda Soedibyo (Universitas Pelita Harapan, 2024)
Driven by rapid urbanization, growing health consciousness, and shifting consumer preferences, the Indonesian bottled drinking water (AMDK) industry has witnessed remarkable expansion. Amid this growth, Le Minerale has emerged as a formidable challenger, disrupting Aqua's long-standing dominance in the market. This study investigates how Social Media Marketing Activities (SMMA) impact Brand Loyalty, mediated by Brand Awareness and Brand Image. Key SMMA elements analyzed include Entertainment, Interactivity, Trendiness, Electronic Word-of-Mouth (e-WOM), and Informativeness. Data were collected from Le Minerale consumers in Medan and analyzed using SPSS. The findings reveal that Interactivity, Trendiness, and e-WOM significantly enhance Brand Awareness, while Interactivity, Trendiness, e-WOM, and Informativeness positively influence Brand Image. Both Brand Awareness and Brand Image, in turn, significantly drive Brand Loyalty. However, Entertainment does not have a direct impact on Brand Image, and Informativeness does not affect Brand Awareness. This research offers valuable insights for marketers aiming to increase customer loyalty in highly competitive markets through the effective use of social media platforms.